Overview of social media utilization as learning resources by junior high school students - Rahma Yanthi (Jurnal Inovasi Guru Indonesia, 2024)
Background: The rapid advancement of information and communication technology has transformed students’ access to learning resources. Social media platforms, as part of digital technology ecosystems, are increasingly utilized by adolescents not only for social interaction but also as informal learning resources. However, empirical evidence regarding how junior high school students utilize social media for academic purposes remains limited. Objective: This study aimed to describe the utilization of social media as learning resources among junior high school students and to identify factors influencing its use. Methods: A descriptive quantitative approach was employed. Data were collected through structured questionnaires distributed to purposively selected junior high school students who actively used social media for learning activities. The instrument examined types of platforms used, frequency of use, learning purposes, and influencing factors. Data were analyzed using descriptive statistics, including frequencies and percentages. Instrument validity and reliability were tested prior to data collection to ensure measurement accuracy. Results: The findings revealed that the majority of students (75%) utilized social media as a learning resource, with YouTube being the most frequently accessed platform (60%), followed by Instagram (20%) and TikTok (15%). Approximately half of the respondents reported daily use for academic purposes. Students indicated that ease of access, availability of visual explanations, and interactive content enhanced their understanding of complex materials. Nevertheless, challenges were identified, including limited digital literacy, difficulty verifying information validity, and distractions from non-academic content. Conclusion: Social media demonstrates substantial potential as an alternative learning resource for junior high school students. However, its effective utilization requires strengthened digital literacy skills, guided supervision from educators and parents, and strategic integration within educational frameworks to minimize misinformation and distraction risks.